Evaluating the incidence of hydrological processes during site formation through orientation analysis. A case study of the middle Palaeolithic Lakeland site of Neumark-Nord 2 (Germany). (April 2016) - García-Moreno, Alejandro; Smith, Geoff M.; Kindler, Lutz; Pop, Eduard; Roebroeks, Wil; Gaudzinski-Windheuser, Sabine; Klinkenberg, Victor
Abstract: Lacustrine localities were attractive environments for Palaeolithic hominins, since they provide a large and broad spectrum of resources. Moreover, they are excellent archives that allow for high-resolution environmental, chronological and archaeological analyses. However, these deposits are often subject to complex formation and post-depositional factors, including water-related processes. Evaluating the influence of hydrological processes in site formation is thus essential to more accurately reconstruct the duration, intensity and types of hominin behaviour within these environments. In this paper we present the orientation analysis of archaeological material from the Last Interglacial site Neumark-Nord 2, Germany. Orientation analysis was done using GIS to calculate the orientation of artefact from digital plans of the excavation surface, which were subsequently tested using circular statistics. The results of the orientation analysis are compared with a hydrological model to check the relation between preferred orientations and reconstructed areas of water flow and accumulation. Results suggest that low-energy hydrological processes could have affected certain areas of the find-bearing deposits at Neumark-Nord 2 but, overall, there is no evidence for either high-energy hydrological processes or a significant movement of parts of the archaeological assemblage. Highlights: We use a GIS to evaluate the orientation of the finds from Neumark-Nord 2. We use a GIS to create a hydrological model of the site. Finds from some areas of the site show preferential orientations. Low-energy processes might have in-situ re-oriented finds at some specific areas. There is no evidence for high-energy hydrological processes having affected the site.